1994
DOI: 10.1093/clinchem/40.3.472
|View full text |Cite
|
Sign up to set email alerts
|

Biological variation in urine samples used for analyte measurements

Abstract: To determine the influence of biological variation on the reliability of data from different types of urine specimens, we measured nine analytes in first-morning, randomly collected, and 24-h samples of urine from 53 healthy individuals (14 men and 39 women). The urines were collected once a week for 10 weeks. The data obtained were used as a basis for specimen collection and to gain insight into the influence of urine quantities in the diagnosis, screening, and monitoring of patients. We found that 24-h urine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 0 publications
0
15
1
Order By: Relevance
“…Endogenous creatinine clearance (CL cr ) is not without limitations either. Coll et al (2) showed serum creatinine levels begin to increase when GFR falls below 75 mL/min/ 1.73 m 2 and therefore, serum creatinine alone may not detect early renal sufficiency in a variety of renal diseases (3).…”
mentioning
confidence: 99%
“…Endogenous creatinine clearance (CL cr ) is not without limitations either. Coll et al (2) showed serum creatinine levels begin to increase when GFR falls below 75 mL/min/ 1.73 m 2 and therefore, serum creatinine alone may not detect early renal sufficiency in a variety of renal diseases (3).…”
mentioning
confidence: 99%
“…31 Reports of values for CV b have led to conclusions regarding the number of samples required for reliable estimates of serum lipids 29 and the medical usefulness of urine for diagnosis and screening of pathologies. 19 When CV b was determined from twice weekly measurements in 20 healthy adults, values for cholesterol, HDL cholesterol, apo A-I, and apo B were less than 8%, cholesterol was less than 10%, and triglyceride was 28%. Intra-subject CV b for Lp(a) ranged from 1% to 50% among the 20 subjects in a direct concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Variability of urinary analytes has been the subject of multiple reports. [16][17][18][19] When 10 overnight urine samples were collected by 10 patients with non-insulin-dependent diabetes mellitus, urinary albumin excretion showed total variability of 12%. 20 A subsequent study found creatinine-normalized urine albumin variability that rose from 19% for normal controls to 61% for children with type I diabetes based on results from 3 consecutive morning urine samples.…”
Section: Introductionmentioning
confidence: 99%
“…Glucose filtration fluxes in the T2DM subjects were profiled using a pooled data set of (i) 24‐hour UGE during SGLT2 inhibitors treatment and (ii) mean daily plasma glucose (MPG) concentrations and eGFR for each treatment arm. When a trial reported only creatinine clearance (CrCl) rather than eGFR, a simple correction (eGFR = 0.9 × CrCl) was used, acknowledging that CrCl overestimates actual GFR by 10% to 20% as a result of the tubular secretion of creatinine …”
Section: Methodsmentioning
confidence: 99%